SURFACE-ACTIVE SUBSTANCES, THEIR TYPES, AND THEIR ROLE IN SYNTHETIC DETERGENTS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2026)
Surface active agent are a class of synthetic compounds. Anionic surfactants are the most aggressive substances, and their content in detergents makes up about 2–5%. These substances can cause immune system disorders in the human body, lead to allergies, and seriously damage the brain, liver, lungs, and kidneys. Phosphates, in turn, facilitate the penetration of surfactants into the human body.